The Implementation of “Kampus Mengajar” Program to Enhance Students Literacy and Numeracy at SDN 100209 TN Sukaramai - Rumiris Pakpahan; Nenni Triana Sinaga; Harpen H.P. Silitonga (Journal of Education and Teaching Learning, 2023)
This study aims to determine the implementation of the “Kampus Mengajar” Program as an effort to improve the students’ quality of literacy and numeracy. The method used for this research is a descriptive qualitative approach. Data collection is done by observation, interviews, and documentation. The result shows that the implementation of “kampus mengajar” program has contributed to enhance students’ literacy, numeracy through three aspects of implementation, namely: conformity between the program and the target group (SDN 100209 TN Sukaramai), conformity between the program and implementing the organization, and conformity between implementing the program of “kampus mengajar” program with the target group.